2018
DOI: 10.1002/path.5007
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor induces renal fibrosis via epidermal growth factor receptor activation

Abstract: Connective tissue growth factor (CCN2/CTGF) is a matricellular protein that is overexpressed in progressive human renal diseases, mainly in fibrotic areas. In vitro studies have demonstrated that CCN2 regulates the production of extracellular matrix (ECM) proteins and epithelial-mesenchymal transition (EMT), and could therefore contribute to renal fibrosis. CCN2 blockade ameliorates experimental renal damage, including diminution of ECM accumulation. We have reported that CCN2 and its C-terminal degradation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 84 publications
(154 reference statements)
1
45
0
Order By: Relevance
“…However, in pathological condition, both beneficial and deleterious roles of EGFR have been observed. In progressive kidney disease, fibrotic renal damage seems to be ameliorated by blocking EGFR [17,18]. However, in the AKI model, renal function recovery and tubular regeneration were both significantly delayed when treated with EGFR tyrosine kinase inhibitor or in the setting of EGFR mutation that induces a reduction in receptor tyrosine kinase activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in pathological condition, both beneficial and deleterious roles of EGFR have been observed. In progressive kidney disease, fibrotic renal damage seems to be ameliorated by blocking EGFR [17,18]. However, in the AKI model, renal function recovery and tubular regeneration were both significantly delayed when treated with EGFR tyrosine kinase inhibitor or in the setting of EGFR mutation that induces a reduction in receptor tyrosine kinase activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The most significantly dysregulated pathways were identified by median p-value over different node penalties ( Figure 5). Among these, known drivers of renal fibrosis including TGF-β, WNT, and EGFR/ERbB signaling stand out (33)(34)(35) . These processes are significantly over-represented in CARNIVAL, but are not significant in GSEA (results not shown).…”
Section: Inferred Dysregulated Cellular Processes By Carnival Dysregmentioning
confidence: 99%
“…In summary, EGFR activation has dual effects in AKI or CKD, ameliorating renal damage in experimental AKI by activating the regenerative process that occurs following acute renal damage through the induction of proliferation and migration of tubular cells. In contrast, EGFR activation exerted deleterious effects on CKD by activation of a fibrotic-related process, as observed in long-term models of renal damage [42, 70, 119, 120] (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, upregulation of the EGFR pathway (including several of its ligands, as TGFA, HBEGF, and CTGF) has been described in human and experimental chronic renal pathologies, including glomerulonephritis, diabetic nephropathy, transplant rejection, and polycystic kidney disease [6365], as well as in experimental models of acute kidney injury (AKI), such as ischemia/reperfusion or folic acid administration [6668]. Intensive research in many experimental studies has shown that EGFR blockade exerts beneficial effects in progressive kidney disease, mainly ameliorating fibrosis [69, 70]. However, EGFR inhibition in AKI models exerts opposite results, presenting deleterious effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation